PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN (Studi Pada Perusahaan Subsektor Food & Beverages yang terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Darmawan, Adi Setya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to examine and analyze the influence of family ownership, foreign ownership, and institutional ownership on firm performance using leverage and firm size as the control variables. The study was conducted on food & beverage companies listed in the Indonesia Stock Exchange in the period of 2011-2015. The sample of this study was determined through purposive sampling method, and 50 observation data (firm-year) were obtained. The analysis is performed using multiple regression model in SPSS. Ownership is measured using the percentage of each ownership in the firms, while performance is measured using the company’s ROA and Tobin's Q. The results of this study indicate that family ownership has a significant negative effect on ROA, but it has no effect on Tobin's Q. Foreign ownership has no effect on both ROA and Tobin's Q. Institutional ownership has no effect on ROA, but it has a significant positive effect on Tobin's Q. Leverage, as a control variable, has a significant negative effect on ROA and Tobin's Q, while firm size, the other control variable, has no effect on both ROA and Tobin's Q.Keywords: Family ownership, foreign ownership, institutional ownership, leverage, firm size, ROA, Tobin's Q